RATIONALE DISCOURSE OF RELIGION AND KNOWLEDGE: PREVENTION OF RELIGIOUS EXTREMISM - Kaldybekov Nurbol; Saduev Ruslan; Shamakhay Saira; Abuov Amrekul; Zhanzhumenov Rustam; Bissenbayeva Zhanat (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article discusses the problems of prevention and prevention of religious extremism and terrorism as well as the solution. At the present stage, religious extremism has become one of the most dangerous and difficult to predict phenomena. After the collapse of the communist ideology, a rapid rise of all religious trends began on the territory of Kazakhstan. In our time, modern society is undergoing a transformation of the value system due to the modernization of social life. The processes of globalization in the economic, political, cultural spheres, drawing the population of countries into migration flows of different nature and level, lead to the complication of the structural ties of specific societies and the entire community as a whole.